Efficacy of PARP Inhibitors, Bevacizumab and Platinum Based Chemotherapy in Treatment Regimen of Patients with BRCA1/2-mutated Ovarian Cancer - Mahnoor Junaid Malik, Salman Jameel Malik (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
N/A